Palm oil derived trimethylolpropane triesters synthetic lubricants and usage in industrial metalworking fluid - Chang, Teck Sin; Yunus, Robiah; Rashid, Umer; Choong, Thomas Shean Yaw; Awang Biak, Dayang Radiah; Muhammad Syam, Azhari (Japan Oil Chemists' Society, 2015)
Trimethylolpropane triesters are biodegradable synthetic lubricant base oil alternative to mineral oils, polyalphaolefins and diesters. These oils can be produced from trimethylolpropane (TMP) and fatty acid methyl esters via chemical or enzymatic catalyzed synthesis methods. In the present study, a commercial palm oil derived winter grade biodiesel (ME18) was evaluated as a viable and sustainable methyl ester source for the synthesis of high oleic trimethylolpropane triesters (HO-TMPTE). ME18 has fatty acid profile containing 86.8% oleic acid, 8.7% linoleic acid with the remaining minor concentration of palmitic acid, stearic acid and linolenic acid. It’s high oleic property makes it superior to produce synthetic lubricant base oil that fulfills both the good low temperature property as well as good oxidative stability. The synthetic base oil produced had a viscosity of 44.3 mm2/s at 40°C meeting the needs for ISO 46 oils. It also exhibited an excellent viscosity index of 219 that is higher than some other commercial brands of trimethylolpropane trioleate. Properties of base oil such as cloud point, density, acid value, demulsibility and soap content were also examined. The oil was then used in the formulation of tapping oil and appraised in term of adaptability, stability and field test performance.